Current concepts in the pathogenesis and treatment of chronic suppurative otitis media. Issue 10 (October 2015) - Mittal, Rahul; Lisi, Christopher V.; Gerring, Robert; Mittal, Jeenu; Mathee, Kalai; Narasimhan, Giri; Azad, Rajeev K.; Yao, Qi; Grati, M'hamed; Yan, Denise; Eshraghi, Adrien A.; Angeli, Simon I.; et al.
Abstract : N/A: Otitis media (OM) is an inflammation of the middle ear associated with infection. Despite appropriate therapy, acute OM (AOM) can progress to chronic suppurative OM (CSOM) associated with ear drum perforation and purulent discharge. The effusion prevents the middle ear ossicles from properly relaying sound vibrations from the ear drum to the oval window of the inner ear, causing conductive hearing loss. In addition, the inflammatory mediators generated during CSOM can penetrate into the inner ear through the round window. This can cause the loss of hair cells in the cochlea, leading to sensorineural hearing loss. Pseudomonas aeruginosa and Staphylococcus aureus are the most predominant pathogens that cause CSOM. Although the pathogenesis of AOM is well studied, very limited research is available in relation to CSOM. With the emergence of antibiotic resistance as well as the ototoxicity of antibiotics and the potential risks of surgery, there is an urgent need to develop effective therapeutic strategies against CSOM. This warrants understanding the role of host immunity in CSOM and how the bacteria evade these potent immune responses. Understanding the molecular mechanisms leading to CSOM will help in designing novel treatment modalities against the disease and hence preventing the hearing loss.